CONCEITO DE CATARSE PARA VIGOTSKI E A DIMENSÃO SENSÍVEL DO CINEMA - Amanda de Melo Omodei; Alvaro Marcel Palomo Alves (Edufatecie, 2020)
This research operates from the theory proposed by Vigotski and reflects how the concept of catharsis can be a tool that produces subjectivity when in association with cinema. The research is constituted in the light of socio-historical psychology and adopts historical-dialectical materialism as a method. For Vygotsky the human is a social being and culture must be interpreted as the raw material for the development of the psyche. It provides us with apparatus and symbolic elements that allow the representation of reality. Thus, the research sought to select nuclei of meaning that could support the discussion about catharsis as a process. The focus group technique was performed with the film "Relatos Selvagens" by Argentine Daminán Szifron as its main instrument, highlighting two cores of meaning: emotion and morality. The first nucleus -emotion-was discussed from the Vigotskian conception of emotions and experiences; the understanding of morals as a second nucleus, on the other hand, allowed a dialogue with Sánchez Vázquez's materialistic view of morals. Therefore, since the individual is a being that develops from mediation, cinema can be considered an instrument of cultural transmission, acting concurrently with catharsis in the sensitive transformation of the individual.